Problematika Seleksi dan Rekrutmen Guru Pemerintah di Indonesia - Andina, Elga; Arifa, Fieka Nurul (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2021)
To date, the implementation of education in Indonesia could not be separated from the problems of teacher governance, non-permanent or honorary teachers, and bureaucratic reforms that affect the quality of education and the working climate within. In an effort to improve the quality of public services by the State Civil Apparatus (ASN), the Ministry of Education and Culture agrees with the Ministry of State Apparatus Utilization and Bureaucratic Reform, as well as the Ministry of Finance to change the recruitment system for government teachers from the recruitment of Candidates for Civil Servants (CPNS) to the recruitment of Government Employees with Work Agreements (PPPK), which in its implementation still leaves several problems with various parties’ pros and cons. This qualitative research uses data from related stakeholders meetings with Commission X DPR RI on January 2021, supported by secondary data from mass media and webinars that discuss the issue of PPPK teachers’ recruitment to answer the following question: how can teachers’ recruitment strategy with PPPK solve the problems of (1) improvement of teachers’ management; (2) solving the issue of honorary teachers; and (3) bureaucratic reform by improving the quality of public services by the State Civil Apparatus (ASN)? It can be concluded that there is a need for a total improvement in the teacher selection and recruitment system, namely (1) based on need; (2) candidates are produced by Teachers Training Institution in supply to field's demand; (3) prioritizing competence and qualifications. AbstrakPenyelenggaraan pendidikan di Indonesia hingga saat ini belum lepas dari persoalan tata kelola guru, guru honorer, dan reformasi birokrasi yang berpengaruh terhadap kualitas pendidikan dan iklim kerja di dalamnya. Dalam upaya peningkatan kualitas layanan publik oleh Aparatur Sipil Negara (ASN), Kementerian Pendidikan dan Kebudayaan sepakat dengan Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi dan Kementerian Keuangan untuk mengubah sistem rekrutmen guru pegawai pemerintah dari penerimaan Calon Pegawai Negeri Sipil (CPNS) menjadi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) yang dalam pelaksanaannya masih menyisakan beberapa masalah dan pro kontra berbagai pihak. Penelitian kualitatif ini menggunakan data rapat stakeholder terkait dengan Komisi X DPR RI selama bulan Januari 2021 dilengkapi data sekunder dari media massa dan webinar yang membahas mengenai isu rekrutmen guru PPPK guna menjawab pertanyaan: bagaimana strategi rekrutmen guru dengan PPPK dapat menyelesaikan permasalahan (1) perbaikan tata kelola guru; (2) penyelesaian isu guru honorer; dan (3) reformasi birokrasi dengan peningkatan kualitas layanan publik oleh ASN? Dapat disimpulkan bahwa perlu ada perbaikan total dalam sistem seleksi dan rekrutmen guru, yaitu: (1) berdasarkan kebutuhan; (2) calon guru diproduksi oleh Lembaga Pendidikan Tenaga Kependidikan sesuai dengan kebutuhan di lapangan; dan (3) mengutamakan kompetensi dan kualifikasi.